Hubungan Peran Pengawas Minum Obat (PMO) dan Motivasi dengan Kepatuhan Minum Obat Tuberkulosis Pada Pasien Tuberkulosis Rawat Jalan di Puskesmas Tarumajaya - Veronica, Rina; Kurniasih, Fitriah (Jurnal Persada Husada Indonesia, 2024)
Tuberculosis (TB) is a disease triggered by a germ called Mycobacterium Tuberculosis, which occurs when the body's immune system decreases. This study aims to determine the relationship between the role of the Medication Monitor (PMO) and motivation and compliance with taking tuberculosis medication in outpatient tuberculosis patients at the Tarumajaya Bekasi Community Health Center in 2021. This research was conducted during May-August 2021. This research uses quantitative research with a cross-sectional approach. The research sample was 30 respondents from all TB patients at the Tarumajaya Bekasi health center and tested using SPSS version 25. Data analysis was carried out univariate and bivariate using the chi-square test.The results of this research show that there is a relationship between the role of the Medication Monitor (PMO) and motivation and compliance with taking tuberculosis medication in outpatient tuberculosis patients at the Tarumajaya Bekasi Community Health Center in 2021. The results of the study using the Pearson chi-square statistical test show that there is a significant relationship between the role of PMO in compliance with taking TB medication with a value of p=0.011 and there is a significant relationship between motivation and compliance with taking TB medication with a value of p=0.000. Based on these results, it can be concluded that the role of PMO and motivation can influence medication adherence in TB patients at the Tarumajaya Bekasi Community Health Center. The suggestion is that TB patients can carry out health behaviors from an early age by always maintaining personal hygiene, the environment in which they live and always carrying out regular health checks at community health centers or other health institutions.